The adverse effects of the methoxsalen and ultraviolent A radiation on spermatogenesis in mice - Mona Farhadi; Homa Mohseni Kouchesfahani; Abass Shockravi; MosaeebForoozanfar; Kazem Parivar (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Different investigation showed that 5-methoxypsoralen and 8- methoxypsoralen reduce birth rates in the rats. Objective: In this study we worked out the effect of methoxsalen together with ultraviolent A (UVA) radiation on mature Balb/C mice spermatogenesis. Materials and Methods: The LD50 standard was determined 160 mg/kg and the UVA dose which causes erythema was calculated 0.046 J/cm2. A sub-lethal dose of 80 mg/kg of methoxsalen solution was injected intrapritoneally to mature mice and after one hour they were exposed to UVA radiation for 20 minutes. Experiments applied included methoxsalen alone, methoxsalen with UVA, UVA alone, sham group (a group received Tween 80), and control group (N=6). In all experimental groups except UVA alone group, injections were carried out, during two consecutive weeks. Serial cross sections (5 µm thickness) were prepared for morphological and histological studies. Tunica albuginea diameter, and number of type A and type B spermatogonia and histological investigation of the testes were measured. Results: Microscopical and statistical analyses showed significant anomalies among the experimental groups compared to control and sham group. These anomalies included decrease the body weight; increase the relative testis weight; and decrease the number of spermapogonia (type A and B), primary spermatocytes, spermatids and sperms in experimental groups I and II compared to control group. Our results showed the number of spermatozoa in experimental group I was 22.6±2.12, in experimental group II was 33.6±2.05 and in control group was 44.3±2.77 (p<0.05). Moreover in some experimental groups (I and II) shrinkage of seminiferous tubules and release of primary spermatocyte and spermatids were observed to the lumen of them. Conclusion: It is concluded from the results of this work that treatment with methoxsalen with UVA can damage and disorganize seminiferous tubules and decrease spermatogenic cells.